The impacts of number of solar photovoltaic units on distribution network losses and voltage profile - Addurat A.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
There is a worldwide concern about environmental issues and fossil fuel depletion. That encourages the world to inject the renewable energy sources to the power system, and this could be safely done at the distribution level using distributed generation units. This paper investigates the impacts of photovoltaic distributed generation (PVDG) on distribution network power losses and voltage profile. The study concentrates on examining the number of PVDGs parameter at different penetration levels while other parameters such as location and size are considered. Modelling and simulation are curried out using MATLAB simulation software. 2020 IEEE.